Quiz Game Hafidz Junior - Sigit Winarso; Joko Priyono; Ridharahman Ibrahim (Syntax Literate, 2023)
Hafidz Junior's game design is based on the influence of globalization on today's younger generation, especially on learning the Quran from an early age. The main objective of the game is to introduce players to the holy book of the Qur'an especially juz 30 of the qur'an and daily prayers. In addition to the main purpose of introducing surahs and daily prayers, players are expected to realize the importance of islamic religious education. In the making of this game, stages are carried out such as pre-production, production, post-production. This game uses the genre of casual game, quiz game. Players must answer the quiz in the quiz arena to get a high score by pressing the answer button in the game arena. Difficulty quiz is meant to slow down towards the end of the game. The platform used for this game is a smartphone with the Android operating system. This platform was chosen because it is easy to play anywhere at any time and at the age of 7 - 13 years can use a smartphone.